The Evaluation of Internal Control System for Market Retribution Collection - Syafruddin Syafruddin; Sri Rahayu; I Putu Gede Diatmika (Universitas Pendidikan Ganesha, 2022)
To evaluate the internal control system for the collection of market levies, the Sumbawa Regency government cooperates with several agencies such as the Department of Transportation, the Department of Cooperatives, Industry and Trade, the Regional Finance and Revenue Management Agency and Bank Rakyat Indonesia with the aim of maximizing Regional Original Income through E-Retribution and avoiding budget leakage and assist the government in accurate economic planning and increase the circulation of money so that it is faster. This study uses a qualitative approach, data collection techniques through observation, interviews and documentation. The results show that the implementation of E-Retribution can make it easier for traders to pay market fees and can solve problems in managing user fees manually, because E-Retribution can be more effective, efficient and more transparent and accountable in increasing Regional Original Income.